2011
DOI: 10.1002/jcp.22777
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase induces stromal cell‐derived factor‐1 expression in human hepatocellular carcinoma cells

Abstract: Both the urokinase-type plasminogen activator (uPA) and the uPA receptor (uPAR) play important roles with regard to hepatocellular carcinoma (HCC) progression and metastasis. Notably, the stromal cell-derived factor-1 (SDF-1) is an important chemokine involved in HCC pathology. However, the influence of uPA on SDF-1 expression in human HCC cells remains unknown. We investigated the mechanisms underlying the modulation of SDF-1 expression through uPA stimulation in human HCC SK-Hep-1 cells. SK-Hep-1 cells stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The activation of the SP-1 downstream of the MAPK or PI3K-Akt pathways is involved in numerous pathological processes, such as inflammation, cancer-cell adhesion, tumor invasion, metastasis, and angiogenesis [23], [33]. Hsu et al reported on the u-PA upregulation by stromal cell-derived factor-1 through ERK and JNK phosphorylation with the modulation of the transcription factors SP-1 and AP-1 activity [34]. In this study, we found that resveratrol inhibited the binding activity of SP-1 to the u-PA promoter in Huh7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the SP-1 downstream of the MAPK or PI3K-Akt pathways is involved in numerous pathological processes, such as inflammation, cancer-cell adhesion, tumor invasion, metastasis, and angiogenesis [23], [33]. Hsu et al reported on the u-PA upregulation by stromal cell-derived factor-1 through ERK and JNK phosphorylation with the modulation of the transcription factors SP-1 and AP-1 activity [34]. In this study, we found that resveratrol inhibited the binding activity of SP-1 to the u-PA promoter in Huh7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AP‐1 activity can be regulated by altering the expression of specific AP‐1 components as a result of the activation of intracellular signaling cascades (Kundu et al, 2006). Previous study also demonstrated that the activation of the ERK pathway is critical for SDF‐1 expression in hepatocellular carcinoma cells (Hsu et al, 2012). Another study showed that SDF‐1 up‐regulation in cardiac cells was counteracted by a p38 inhibitor (Hohensinner et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…148 Moreover, the CXCL12/CXCR4 axis was found to cross talk with other relevant intrahepatic pathways, including osteopontin and urokinase. 149,150 More recently, this system has also been linked to the biology of tumor-initiating cells expressing the progenitor marker OV6. CXCL12 provoked an expansion of the OV6-positive population and sustained their stemness properties, 151 while receptor antagonist or CXCR4 small interfering RNAs blocked these effects.…”
Section: Progression and Regression Of Fibrosismentioning
confidence: 99%